Ecological Tax Reform and Efficiency of Taxation: A Public Good Perspective - Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1996)
The basic focus of this paper is to look at ecological tax reform from a public good perspective rather than from a Pigouvian externality cum tax reform perspective. Our point of departure is the insight, aptly expressed by Heller and Starrett (1976, p. l 0), e. g., that "one can think of externalities as nearly synonymous with non existence of markets". In their view an externality is "a situation in which the private economy lacks sufficient incentives to create a potential market in some good and the non existence of this market results in losses in Pareto efficiency" (ibid.). Thinking of externalities or rather public goods in terms of (non existing) markets requires, first of all, to identify the commodities traded on these fictitious markets. In our context these goods are 'environmental quality' and 'nature's assimilative services' the former being a public good and the latter a private good. For reference purposes we build a simple model in which all disincentives of market creation are assumed to be absent: Nature's fixed endowment of assimilative services is privately owned and is sold to two different users, to the producer of environmental quality and to the consumption good industry. This fancy scenario of a complete set of competitive markets is known to constitute a first-best world with full internalization of the environmental externality. Government has no useful role to play since even the public good 'environmental quality' is privately provided in an efficient way - ignoring all the well-known problems of demand revelation and free riding.
Keywords: 330